Electrolyte, electrolyte, preparation method of electrolyte and lithium ion battery
By using electrolyte containing sulfide monomers with dynamic reversible disulfide bonds in lithium-ion batteries, the self-healing problem after the interface film of solid electrolyte in lithium-ion batteries is solved, and the circulation and electrochemical performance of the battery are improved.
Patent Information
- Application Number
- CN202411818550.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-12-10
AI Technical Summary
During the long-term cycle charging and discharging process of lithium-ion batteries, the volume changes of the positive electrode material particles and negative electrode material particles lead to rupture of the solid electrolyte interface film, and the electrolyte cannot be effectively repaired, affecting the cycling and electrochemical performance of the battery.
An electrolyte solution is provided, including an organic solvent, a lithium salt and a polymer monomer, wherein the polymer monomer consists of acrylate monomer and a sulfide monomer. The sulfide monomer has a dynamic reversible disulfide bond, which can reform the interface protective layer at the cracks of the solid electrolyte interface film to achieve self-healing.
The solid polymer interface film is formed on the surface of the battery material by polymer monomers, which reduces the contact between the positive and negative electrode materials and the battery components, inhibits side reactions and gas generation, and improves the cycling and electrochemical properties of the battery.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to an electrolyte, an electrolyte and a preparation method thereof, and a lithium ion battery. Background Art
[0002] Lithium-ion batteries with high energy density, high power density, long life, and no memory are being widely used in smart homes, smart wearables, smart communication tools, and the Internet of Everything. Gel electrolytes have the advantages of high mechanical strength, good electrochemical stability, and good thermal stability, and are used in lithium-ion batteries. Gel electrolytes are usually prepared by in-situ polymerization. During the in-situ polymerization process, the polymer monomers in the electrolyte can participate in the positive electrode film formation and the negative electrode film formation, and form a layer of solid electrolyte interface film on the surface of the positive electrode material particles and the negative electrode material particles.
[0003] In the related art, during the long-term cycle charge and discharge process of lithium-ion batteries, the volume of the positive electrode material particles and the negative electrode material particles will change, causing the solid electrolyte interface film (Sol id Electrolyte Interphase, SEI) wrapped on the surface of the positive electrode material particles and the negative electrode material particles to rupture. After the solid electrolyte interface film is ruptured, the electrolyte's repair effect on the solid electrolyte interface film is not ideal, affecting the battery's cycle performance and electrochemical performance. Summary of the invention
[0004] The embodiments of the present invention provide an electrolyte, an electrolyte and a preparation method thereof, and a lithium-ion battery, which can improve the technical problem that after the solid electrolyte interface film on the surface of the positive electrode material particles and the negative electrode material particles is ruptured, the electrolyte has an unsatisfactory repair effect on the solid electrolyte interface film.
[0005] In a first aspect, an embodiment of the present invention provides an electrolyte, including an organic solvent, a lithium salt and a polymer monomer;
[0006] Wherein, the polymer monomers include acrylic ester monomers and thioether monomers, and the structural formula of the thioether monomers is shown in Formula I:
[0007]
[0008] wherein n is selected from 2, 3, 4, 5, 6, 7 or 8;
[0009] y and z are each independently selected from 0, 1, 2, 3, 4, 5 or 6;
[0010] The substituents R1-R6 are each independently selected from a hydrogen atom, a halogen, a cyano group, an isocyanate group, a C1-C18 substituted or unsubstituted straight or branched alkyl group, a C1-C10 substituted or unsubstituted straight or branched alkoxy group, a C3-C10 straight or branched carboxylate group, a C3-C10 straight or branched acrylate group, a C3-C10 straight or branched alkenyl group, a C3-C10 straight or branched alkynyl group, a C6-C26 unsubstituted aryl group, a C6-C26 aryl group substituted by an alkyl group, an alkoxy group, a hydroxyl group, a cyano group and / or a halogen, a C6-C26 heterocyclic aryl group substituted by an alkyl group, an alkoxy group, a hydroxyl group, a cyano group and / or a halogen, a C7-C27 unsubstituted benzyl group, a C7-C27 benzyl group substituted by an alkyl group, an alkoxy group, a hydroxyl group, a cyano group and / or a halogen, or a combination of these groups.
[0011] In one embodiment, n is selected from 2 or 3; and / or
[0012] The y and z are each independently selected from 0 or 1; and / or
[0013] The substituents R1-R6 are each independently selected from a hydrogen atom and / or a C1-C18 straight or branched alkyl group.
[0014] In one embodiment, the sulfide monomer includes at least one of diethylene disulfide, diallyl disulfide, and diallyl trisulfide; and / or
[0015] The acrylate monomer includes at least one of pentaerythritol tetraacrylate, ethoxylated trimethylolpropane triacrylate, dipentaerythritol hexaacrylate, ditrimethylolpropane tetraacrylate, methyl methacrylate, butyl methacrylate, polyethylene glycol methyl diacrylate, polyethylene glycol methyl diacrylate, and cyanoacrylate.
[0016] In one embodiment, the mass percentage of the polymer monomer in the electrolyte is 2%-34%; and / or
[0017] The mass percentage of the acrylic ester monomer in the polymer monomer is 30%-85%, and the mass percentage of the thioether monomer in the polymer monomer is 15%-65%.
[0018] In one embodiment, the polymer monomer further includes a thiol monomer.
[0019] In one embodiment, the thiol monomer includes at least one of 1,3-ethanedithiol, benzenethiol, dodecanethiol, 1,4-butanedithiol, 1,6-hexanedithiol, 1,8-octanedithiol, 1,5-pentanedithiol, and 2,3-butanedithiol; and / or
[0020] The mass percentage of the thiol monomer in the polymer monomer is 0-65%.
[0021] In one embodiment, the electrolyte further includes an initiator and / or an additive.
[0022] In one embodiment, the organic solvent includes at least one of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, ethylene carbonate, vinylene carbonate, methyl formate, ethyl formate, ethyl acetate, methyl propionate, ethylene glycol dimethyl ether, polyethylene glycol dimethyl ether, ethylene glycol tert-butyl ether, diethylene glycol monomethyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, hexaethylene glycol dimethyl ether, and heptapolyethylene glycol; and / or
[0023] The lithium salt comprises at least one of lithium nitrate, lithium hexafluorophosphate, lithium perchlorate, lithium difluorooxalatoborate, lithium trifluoromethanesulfonyl imide, lithium bisfluorosulfonyl imide, lithium diacetate borate, lithium tetrafluoroborate, and lithium difluorophosphate; and / or
[0024] The initiator includes azobisisobutyronitrile, azobisisovaleronitrile, azobisisoheptanenitrile, diethyl azodicarboxylate, di-2-methoxyethyl azodicarboxylate, di-tert-butyl azodicarboxylate, diisopropyl azodicarboxylate, dibenzyl azodicarboxylate, dimethyl azodiisobutyrate, dimethyl azobenzene-4,4'-dicarboxylate, dibenzyl azodihydroxy acid ester, azobisacyldipiperidine, azodicarbonyldimorphine, azodicarbonamide, azobenzene, 4,4-azopyridine, At least one of diethyl 4,4'-azodibenzoate, 4-methyl 4-dimethylaminoazobenzene, 3,3-dimethylazobenzene, phenylazomalononitrile, tert-azobutane, methyl red, methyl orange, tropaeolum orange O, tert-butyl ketone peroxide, cyclohexanone peroxide, dimethanesulfonyl peroxide, tert-butyl perbenzoate, tert-butyl peroxyisopropyl carbonate, 2-butyl ketone peroxide, dilauroyl peroxide, benzoyl peroxide, lithium persulfate, and lithium peroxymonosulfate; and / or
[0025] The additive comprises at least one of vinylene carbonate, fluoroethylene carbonate, triethyl phosphite, 1,3-propane sultone, ethylene sulfite, 1,3,2-dioxazolethiophene-2,2-dioxide, 1,4-butane sultone, phenyl methanesulfonate, adiponitrile, 3-methoxypropionitrile, hexane-1,3,6-tricarboxonitrile, ethylene glycol bis(propionitrile) ether, hexamethyldisilazane, and trimethylsilyldiethylamine; and / or
[0026] The mass percentage of the organic solvent in the electrolyte is 30%-80%; and / or
[0027] The mass percentage of the lithium salt in the electrolyte is 5%-20%; and / or
[0028] The mass percentage of the initiator in the electrolyte is 0.01%-3%; and / or
[0029] The mass percentage of the additive in the electrolyte is 2%-30%.
[0030] In a second aspect, an embodiment of the present invention provides an electrolyte, wherein the electrolyte is prepared from the electrolyte solution as described above.
[0031] In a third aspect, an embodiment of the present invention provides a method for preparing an electrolyte, the method comprising the following steps:
[0032] providing an electrolyte as described above;
[0033] The electrolyte is injected into the battery cell, left to stand, and heated to solidify to obtain the electrolyte.
[0034] In one embodiment, the method for preparing the electrolyte comprises the following steps: mixing a formulated amount of an organic solvent, a lithium salt, a polymer monomer and other raw materials to obtain the electrolyte.
[0035] In one embodiment, the other raw materials further include a formulated amount of initiator and / or additive; and / or
[0036] The mixing is carried out in an argon atmosphere, a nitrogen atmosphere or a dry air atmosphere, and / or the mixing temperature is 20° C.-30° C., and / or the mixing time is 0.5 h-3 h; and / or
[0037] The standing temperature is 20°C-35°C, and / or the standing time is 24h-72h; and / or
[0038] The temperature of the heating and curing is 45° C.-120° C., and / or the time of the heating and curing is 8 h-60 h.
[0039] In a fourth aspect, an embodiment of the present invention provides a lithium-ion battery, comprising the electrolyte as described above or an electrolyte prepared by the method as described above.
[0040] Beneficial effects of the embodiments of the present invention:
[0041] In an embodiment of the present invention, the polymer monomers include acrylate monomers and thioether monomers. The acrylate monomers and thioether monomers can undergo polymerization reactions to generate solid polymers. At the same time, the acrylate monomers and thioether monomers participate in the positive electrode film formation and the negative electrode film formation during the polymerization reaction, and can form a layer of solid electrolyte interface film containing solid polymers on the surface of the positive electrode material particles and the negative electrode material particles. The solid electrolyte interface film can reduce the contact between the positive and negative electrode materials and the organic solvents, lithium salts and other components in the battery, and inhibit the dissolution and precipitation of transition metals and the release of lattice oxygen, thereby reducing the generation of side reactions inside the battery; when the solid electrolyte interface film on the surface of the positive electrode material particles and the negative electrode material particles is broken, since the solid polymer contains disulfide bonds, the disulfide bonds have dynamic reversibility and covalent bond stability, and the solid polymer interface protection layer can be re-formed at the cracks of the solid electrolyte interface film, thereby effectively realizing the self-repair of the solid electrolyte interface film, reducing the contact between the positive and negative electrode active substances and the organic solvents, lithium salts and other components and the generation of side reactions, and improving the cycle performance and electrochemical performance of the battery. DETAILED DESCRIPTION
[0042] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention. In the present invention, unless otherwise specified, the directional words used, such as "upper" and "lower", generally refer to the upper and lower parts of the device in actual use or working state, while "inside" and "outside" refer to the outline of the device.
[0043] In the related art, after the solid electrolyte interface membrane on the surface of the positive electrode material particles and the negative electrode material particles of the lithium-ion battery is broken, the electrolyte cannot effectively repair the solid electrolyte interface membrane, which affects the cycle performance and electrochemical performance of the battery and needs further improvement.
[0044] To solve the above problems, an embodiment of the present application provides an electrolyte, the electrolyte comprising an organic solvent, a lithium salt and a polymer monomer; wherein the polymer monomer comprises an acrylate monomer and a thioether monomer, and the structural formula of the thioether monomer is shown in Formula I:
[0045]
[0046] wherein n is selected from 2, 3, 4, 5, 6, 7 or 8;
[0047] y and z are each independently selected from 0, 1, 2, 3, 4, 5 or 6;
[0048] The substituents R1-R6 are each independently selected from a hydrogen atom, a halogen, a cyano group, an isocyanate group, a C1-C18 substituted or unsubstituted straight or branched alkyl group, a C1-C10 substituted or unsubstituted straight or branched alkoxy group, a C3-C10 straight or branched carboxylate group, a C3-C10 straight or branched acrylate group, a C3-C10 straight or branched alkenyl group, a C3-C10 straight or branched alkynyl group, a C6-C26 unsubstituted aryl group, a C6-C26 aryl group substituted by an alkyl group, an alkoxy group, a hydroxyl group, a cyano group and / or a halogen, a C6-C26 heterocyclic aryl group substituted by an alkyl group, an alkoxy group, a hydroxyl group, a cyano group and / or a halogen, a C7-C27 unsubstituted benzyl group, a C7-C27 benzyl group substituted by an alkyl group, an alkoxy group, a hydroxyl group, a cyano group and / or a halogen, or a combination of these groups.
[0049] In this embodiment, the polymer monomers include acrylate monomers and thioether monomers; on the one hand, the acrylate monomers and the thioether monomers can undergo polymerization reaction to generate solid polymers. At the same time, the acrylate monomers and the thioether monomers participate in the positive electrode film formation and the negative electrode film formation during the polymerization reaction, and can form a layer of solid electrolyte interface film containing solid polymers on the surface of the positive electrode material particles and the negative electrode material particles. The solid electrolyte interface film can reduce the contact between the positive and negative electrode materials and the organic solvents, lithium salts and other components in the battery, and inhibit the dissolution of transition metals and the release of lattice oxygen, reduce the generation of side reactions and gas generation inside the battery, reduce the loss of battery capacity, and improve the battery life. The thermal runaway temperature of the battery is reduced; on the other hand, the solid polymer contains disulfide bonds. When the solid electrolyte interface film on the surface of the positive electrode material particles and the negative electrode material particles is broken, the disulfide bonds are dynamically reversible and can reform the solid polymer interface protection layer at the cracks of the solid electrolyte interface film, thereby effectively self-repairing the solid electrolyte interface film and improving the cycle performance and electrochemical performance of the battery; in addition, the sulfide monomers containing carbon-carbon double bonds have high reactivity, which can increase the conversion rate of the reaction between sulfide monomers and acrylate monomers, reduce the reaction temperature, reduce the residual polymer monomers in the battery and the side effects of the residual monomers on the battery, and increase the service life of the battery.
[0050] In one embodiment, n is selected from 2 or 3.
[0051] In one embodiment, y and z are each independently selected from 0 or 1.
[0052] In one embodiment, the substituents R1-R6 are each independently selected from a hydrogen atom and / or a C1-C18 linear or branched alkyl group.
[0053] In one embodiment, the sulfide monomer includes at least one of diethylene disulfide, diallyl disulfide, and diallyl trisulfide. In this embodiment, on the one hand, the sulfide monomer can be directly purchased commercially, and the raw materials are easy to obtain, which can save the synthesis steps of the sulfide monomer and simplify the production process of the battery; on the other hand, the sulfide monomer does not contain gas-generating groups such as hydroxyl and amino groups. When the sulfide monomer remains in the battery, it is not easy to generate gas, which further ensures the cycle performance and safety performance of the battery.
[0054] In one embodiment, the acrylate monomer includes at least one of pentaerythritol tetraacrylate, ethoxylated trimethylolpropane triacrylate, dipentaerythritol hexaacrylate, ditrimethylolpropane tetraacrylate, methyl methacrylate, butyl methacrylate, polyethylene glycol methyl diacrylate, polyethylene triethylene glycol methyl diacrylate, and cyanoacrylate. In this embodiment, the raw materials of the acrylate monomer are easily available and have low cost, which can reduce the raw material cost of the battery.
[0055] In one embodiment, the mass percentage of the polymer monomer in the electrolyte is 2%-34%. Optionally, the mass percentage of the polymer monomer in the electrolyte is any one of 2%, 5%, 10%, 15%, 20%, 25%, 30%, 34%, etc. or a range between any two. In this embodiment, if the content of the polymer monomer is too little, the coating effect of the generated solid polymer on the positive electrode material particles and the negative electrode material particles is not ideal, and at the same time, the repair effect of the disulfide bond in the solid polymer on the solid electrolyte interface film is reduced, resulting in the poor stability of the solid electrolyte interface film on the surface of the positive electrode material particles and the negative electrode material particles. The positive electrode material particles and the negative electrode material particles are prone to side reactions with organic solvents, lithium salts and other components in the battery, consuming positive and negative electrode materials and lithium ions; if the content of the polymer monomer is too much, it is easy to cause the molecular weight of the solid polymer to be too large and the increase of side reactions, thereby reducing the electrochemical performance of the battery.
[0056] In one embodiment, the mass percentage of the acrylate monomer in the polymer monomer is 30%-85%, and the mass percentage of the thioether monomer in the polymer monomer is 15%-65%. Optionally, the mass percentage of the acrylate monomer in the polymer monomer is any one of 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, etc., or any two thereof; the mass percentage of the thioether monomer in the polymer monomer is any one of 15%, 20%, 25%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, etc., or any two thereof.
[0057] In this embodiment, if the content of acrylate monomers is too much and the content of thioether monomers is too little, it is easy to cause too few reversible repair sites in the solid polymer, the disulfide bond repair effect on the solid electrolyte interface film is not ideal, the precipitation of transition metal ions during the battery cycle increases, the generation of side reactions inside the battery increases, and the battery performance is reduced; if the content of acrylate monomers is too little and the content of thioether monomers is too much, it is easy to cause the mechanical strength of the solid electrolyte interface film generated on the surface of the positive electrode material particles and the negative electrode material particles to be too low. When the solid electrolyte interface film responds to the volume change of the positive and negative electrode material particles, the solid electrolyte interface film is prone to serious rupture, resulting in an unsatisfactory self-repair effect. At the same time, due to the high cost of thioether monomers, it is easy to increase the production cost of the battery.
[0058] In one embodiment, the polymer monomer further comprises a thiol monomer. In this embodiment, on the one hand, after the reaction of the thioether monomer and the acrylate monomer is completed, a small amount of thioether monomer usually remains, and the thiol monomer can react with the thioether monomer to further consume the thioether monomer. At the same time, since the thioether monomer contains a carbon-carbon double bond, the thioether monomer has a high reactivity, which can improve the conversion rate of the reaction between the thioether monomer and the thiol monomer, reduce the residual polymer monomer, and further reduce the side reaction between the residual polymer monomer and the electrode active substance; on the other hand, the thiol monomer can exchange with the disulfide bond on the solid polymer, causing part of the solid polymer to fold, and the folded solid polymer gathers at the interface between the positive and negative electrode material particles and the electrolyte, and can be coated with a nano film layer on the surface of the positive and negative electrode material particles, and the nano film layer is conducive to reducing the contact between the positive and negative electrode material particles and components such as lithium salts and organic solvents, and inhibiting the dissolution and precipitation of transition metals and the release of lattice oxygen, reducing the occurrence of side reactions and gas generation inside the battery, reducing the loss of battery capacity, and improving the thermal runaway temperature and cycle life of the battery.
[0059] In one embodiment, the thiol monomer includes at least one of 1,3-ethanedithiol, benzenethiol, dodecanethiol, 1,4-butanedithiol, 1,6-hexanedithiol, 1,8-octanedithiol, 1,5-pentanedithiol, and 2,3-butanedithiol.
[0060] In one embodiment, the mass percentage of the thiol monomer in the polymer monomer is 0-65%. Optionally, the mass percentage of the thiol monomer in the polymer monomer is any one of 0, 10%, 20%, 30%, 40%, 50%, 60%, 65%, etc. or a range between any two. In this embodiment, if the content of the thiol monomer is too much, it is easy to cause an increase in the residual thiol monomer, thereby increasing the side reaction between the thiol monomer and the electrode, causing the battery to produce gas and damage the capacity; if the content of the thiol monomer is too little, the effect of reducing the residual amount of the thioether monomer is not ideal.
[0061] In one embodiment, the electrolyte further includes an initiator and / or an additive.
[0062] In one embodiment, the organic solvent includes at least one of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, ethylene carbonate, vinylene carbonate, methyl formate, ethyl formate, ethyl acetate, methyl propionate, ethylene glycol dimethyl ether, polyethylene glycol dimethyl ether, ethylene glycol tert-butyl ether, diethylene glycol monomethyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, hexaethylene glycol dimethyl ether, and heptaethylene glycol.
[0063] In one embodiment, the lithium salt includes at least one of lithium nitrate, lithium hexafluorophosphate, lithium perchlorate, lithium difluorooxalatoborate, lithium trifluoromethanesulfonyl imide, lithium bisfluorosulfonyl imide, lithium diacetate borate, lithium tetrafluoroborate, and lithium difluorophosphate.
[0064] In one embodiment, the initiator includes azobisisobutyronitrile, azobisisovaleronitrile, azobisisoheptanenitrile, diethyl azodicarboxylate, di-2-methoxyethyl azodicarboxylate, di-tert-butyl azodicarboxylate, diisopropyl azodicarboxylate, dibenzyl azodicarboxylate, dimethyl azodiisobutyrate, dimethyl azobenzene-4,4'-dicarboxylate, dibenzyl azodihydroxy acid ester, azobisacyldipiperidine, azobiscarbonyldimorphine, azodicarbonamide, azobenzene, 4,4-dicarboxylic acid At least one of azopyridine, diethyl 4,4'-azodibenzoate, 4-methyl 4-dimethylaminoazobenzene, 3,3-dimethylazobenzene, phenylazomalononitrile, tert-azobutane, methyl red, methyl orange, tropaeolum orange O, tert-butyl ketone peroxide, cyclohexanone peroxide, dimethanesulfonyl peroxide, tert-butyl perbenzoate, tert-butyl peroxyisopropyl carbonate, 2-butyl ketone peroxide, dilauroyl peroxide, benzoyl peroxide, lithium persulfate, and lithium permonosulfate.
[0065] In one embodiment, the additive includes at least one of vinylene carbonate, fluoroethylene carbonate, triethyl phosphite, 1,3-propane sultone, ethylene sulfite, 1,3,2-dioxazolethiophene-2,2-dioxide, 1,4-butane sultone, phenyl methanesulfonate, adiponitrile, 3-methoxypropionitrile, hexane-1,3,6-tricarboxonitrile, ethylene glycol bis(propionitrile) ether, hexamethyldisilazane, trimethylsilyldiethylamine, etc.
[0066] In one embodiment, the mass percentage of the organic solvent in the electrolyte is 30%-80%. Optionally, the mass percentage of the organic solvent in the electrolyte is any one of 30%, 40%, 50%, 60%, 70%, 80%, etc. or a range between any two.
[0067] In one embodiment, the mass percentage of the lithium salt in the electrolyte is 5%-20%. Optionally, the mass percentage of the lithium salt in the electrolyte is any one of 5%, 8%, 10%, 14%, 18%, 20%, etc. or a range between any two.
[0068] In one embodiment, the mass percentage of the initiator in the electrolyte is 0.01%-3%. Optionally, the mass percentage of the initiator in the electrolyte is any one of 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, etc., or any range between two of them.
[0069] In one embodiment, the mass percentage of the additive in the electrolyte is 2%-30%. Optionally, the mass percentage of the additive in the electrolyte is any one of 2%, 5%, 10%, 15%, 20%, 25%, 30%, etc., or a range between any two.
[0070] The present application also provides an electrolyte, which is prepared from the above-mentioned electrolyte.
[0071] In this embodiment, the solid polymer in the electrolyte contains disulfide bonds. When the solid electrolyte interface membrane on the surface of the positive electrode material particles and the negative electrode material particles is broken, the disulfide bonds are dynamically reversible and can reform the solid polymer interface protection layer at the cracks of the solid electrolyte interface membrane, thereby effectively self-repairing the solid electrolyte interface membrane and improving the cycle performance and electrochemical performance of the battery.
[0072] The present application also provides a method for preparing an electrolyte, comprising the following steps:
[0073] S1, providing the electrolyte as described above;
[0074] S2. Inject the electrolyte into the battery cell, let it stand, heat and solidify to obtain the electrolyte.
[0075] In one embodiment, the method for preparing the electrolyte comprises the following steps:
[0076] The organic solvent, lithium salt, polymer monomer and other raw materials in a prescribed amount are mixed to obtain an electrolyte.
[0077] In one embodiment, other raw materials further include a formulated amount of initiator and / or additives.
[0078] In one embodiment, the mixing can be performed in an argon atmosphere, a nitrogen atmosphere, or a dry air atmosphere, which is not limited in the present application.
[0079] In one embodiment, the mixing temperature is 20°C-30°C, and / or the mixing time is 0.5h-3h. Optionally, the mixing temperature can be any one of 20°C, 22°C, 24°C, 26°C, 28°C, 30°C, etc., or a range between any two thereof; the mixing time can be any one of 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, etc., or a range between any two thereof.
[0080] In one embodiment, the standing temperature is 20°C-35°C, and / or the standing time is 24h-72h. Optionally, the standing temperature can be any one of 20°C, 22°C, 24°C, 26°C, 28°C, 30°C, 35°C, etc., or a range between any two thereof; the standing time can be any one of 24h, 30h, 35h, 40h, 50h, 60h, 70h, 72h, etc., or a range between any two thereof.
[0081] In one embodiment, the temperature of the heating curing is 45°C-120°C, and / or the time of the heating curing is 8h-60h. Optionally, the temperature of the heating curing can be any one of 45°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, etc., or a range between any two thereof; the time of the heating curing can be any one of 8h, 10h, 20h, 30h, 40h, 50h, 60h, etc., or a range between any two thereof.
[0082] The present application also provides a lithium-ion battery, which includes the electrolyte as described above or the electrolyte prepared by the method as described above.
[0083] In this embodiment, the type of lithium-ion battery is not limited, and the lithium-ion battery can be one of a ternary soft-pack battery, a ternary steel-shell battery, a lithium cobalt oxide soft-pack battery, and a lithium cobalt oxide steel-shell battery.
[0084] The above scheme is further described below in conjunction with specific implementation examples. The preferred embodiments of the present application are described in detail as follows:
[0085] Example 1
[0086] This embodiment provides an electrolyte, including: a lithium salt, an organic solvent, an additive, an initiator and a polymer monomer;
[0087] Wherein, the lithium salt is lithium hexafluorophosphate, and the mass percentage of the lithium salt in the electrolyte is 10.6%;
[0088] The organic solvent is composed of ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate, the volume ratio of ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate is 1:1:1, and the mass percentage of the organic solvent in the electrolyte is 68%;
[0089] The additive is composed of vinylene carbonate and 1,3-propane sultone, and the mass percentage of the additive in the electrolyte is 3%;
[0090] The initiator is azobisisobutyronitrile, and the mass percentage of the initiator in the electrolyte is 0.4%;
[0091] The polymer monomer consists of diallyl disulfide and pentaerythritol tetraacrylate, the mass percentage of diallyl disulfide in the polymer monomer is 30%, the mass percentage of pentaerythritol tetraacrylate in the polymer monomer is 70%, and the mass percentage of the polymer monomer in the electrolyte is 18%.
[0092] This embodiment also provides a method for preparing a lithium battery, the specific method is:
[0093] (1) A negative electrode material graphite, a conductive agent acetylene black, and a binder sodium carboxymethyl cellulose and styrene-butadiene rubber were prepared into a slurry in a mass percentage of 97:1:0.5:1.5, coated on a copper foil current collector, and vacuum dried to obtain a negative electrode sheet; a positive electrode material NCM811 (LiNi 0.8 Co 0.1 Mn 0.1 ), a conductive agent acetylene black and a binder polyvinylidene fluoride are prepared into a slurry in a mass ratio of 96:2:2, coated on an aluminum foil current collector, and dried to obtain a positive electrode sheet; the positive electrode sheet, the negative electrode sheet, and the separator are assembled to obtain a battery cell.
[0094] (2) Under an argon atmosphere, the lithium salt, organic solvent, additive, initiator and polymer monomer in the above-mentioned formula are mixed at an ambient temperature of 20° C. to obtain an electrolyte.
[0095] (3) Injecting the electrolyte precursor into the battery cell, vacuum packaging, standing, and heating to cure to obtain the electrolyte, wherein the vacuum degree of the vacuum packaging is -90 kPa, the standing temperature is 30° C., the standing time is 30 h, the heating curing temperature is 70° C., and the heating curing time is 32 h.
[0096] (4) Cooling the battery cell containing the electrolyte to room temperature, forming it, and dividing its capacity to obtain a lithium-ion battery.
[0097] Example 2
[0098] The difference between Example 2 and Example 1 is:
[0099] The polymer monomer consists of diethylene disulfide and pentaerythritol tetraacrylate, the mass percentage of diethylene disulfide in the polymer monomer is 30%, the mass percentage of pentaerythritol tetraacrylate in the polymer monomer is 70%, and the rest is the same as in Example 1.
[0100] Example 3
[0101] The difference between Example 3 and Example 1 is:
[0102] The polymer monomer consists of diallyl disulfide and dipentaerythritol hexaacrylate, the mass percentage of diallyl disulfide in the polymer monomer is 30%, the mass percentage of dipentaerythritol hexaacrylate in the polymer monomer is 70%, and the rest is the same as in Example 1.
[0103] Example 4
[0104] The difference between Example 4 and Example 1 is:
[0105] The polymer monomer consists of diallyl disulfide, pentaerythritol tetraacrylate and 1,4-butanedithiol. Based on the total mass of the polymer monomer as 100%, the mass fraction of diallyl disulfide is 30%, the mass fraction of pentaerythritol tetraacrylate is 60%, and the mass fraction of 1,4-butanedithiol is 10%. The rest is the same as in Example 1.
[0106] Example 5
[0107] The difference between Example 5 and Example 1 is:
[0108] The polymer monomer consists of diallyl disulfide, pentaerythritol tetraacrylate and benzenethiol. Based on the total mass of the polymer monomer as 100%, the mass fraction of diallyl disulfide is 30%, the mass fraction of pentaerythritol tetraacrylate is 60%, and the mass fraction of benzenethiol is 10%. The rest is the same as in Example 1.
[0109] Example 6
[0110] The difference between Example 6 and Example 1 is:
[0111] The mass percentage of the polymer monomer in the electrolyte is 2%, and the rest is the same as in Example 1.
[0112] Example 7
[0113] The difference between Example 7 and Example 1 is:
[0114] The mass percentage of the polymer monomer in the electrolyte is 34%, and the rest is the same as in Example 1.
[0115] Example 8
[0116] The difference between Example 8 and Example 1 is:
[0117] The polymer monomer consists of diallyl disulfide and pentaerythritol tetraacrylate. Based on the total mass of the polymer monomer as 100%, the mass fraction of diallyl disulfide is 15%, the mass fraction of pentaerythritol tetraacrylate is 85%, and the rest is the same as in Example 1.
[0118] Example 9
[0119] The difference between Example 9 and Example 1 is:
[0120] The polymer monomer consists of diallyl disulfide and pentaerythritol tetraacrylate. Based on the total mass of the polymer monomer as 100%, the mass fraction of diallyl disulfide is 65%, the mass fraction of pentaerythritol tetraacrylate is 35%, and the rest is the same as in Example 1.
[0121] Example 10
[0122] The difference between Example 10 and Example 1 is:
[0123] The polymer monomer consists of diallyl disulfide and pentaerythritol tetraacrylate, the mass percentage of diallyl disulfide in the polymer monomer is 75%, the mass percentage of pentaerythritol tetraacrylate in the polymer monomer is 25%, and the rest is the same as in Example 1.
[0124] Comparative Example 1
[0125] The difference between Comparative Example 1 and Example 1 is:
[0126] The polymer monomer is composed of diallyl disulfide, and the mass percentage of diallyl disulfide in the polymer monomer is 100%. The rest is the same as in Example 1.
[0127] Comparative Example 2
[0128] The difference between Comparative Example 2 and Example 1 is:
[0129] The polymer monomer consists of pentaerythritol tetraacrylate, the mass percentage of pentaerythritol tetraacrylate in the polymer monomer is 100%, and the rest is the same as in Example 1.
[0130] Comparative Example 3
[0131] The difference between Comparative Example 3 and Example 1 is:
[0132] The polymer monomer consists of diphenyl disulfide and pentaerythritol tetraacrylate, the mass percentage of diphenyl disulfide in the polymer monomer is 30%, the mass percentage of pentaerythritol tetraacrylate in the polymer monomer is 70%, and the rest is the same as in Example 1.
[0133] Test Method
[0134] The performance of the lithium ion batteries obtained in Examples 1 to 10 and Comparative Examples 1 to 3 was tested, and the specific method is as follows:
[0135] (1) Cycle performance: Full battery test of lithium-ion batteries at 25°C with constant current and constant voltage charging and discharging at a current density of 1C, with a charge and discharge voltage window of 2.8V-4.2V.
[0136] (2) Rate performance: The lithium-ion battery is charged at a current density of 1C and discharged at a current density of 3C with a constant current and constant voltage for full battery testing. The charge and discharge voltage window is 2.8V-4.2V.
[0137] (3) 130°C thermal abuse pass rate: The lithium-ion battery is heated from room temperature (25°C) to 130°C at a rate of 5°C / min, and then kept at 130°C for 1 hour. If there is no fire or explosion, the battery is considered to have passed the test.
[0138] The test results are shown in Table 1 below:
[0139] Table 1
[0140]
[0141] Based on the test results of the above embodiments and comparative examples, it can be seen that the lithium-ion batteries prepared in Examples 1 to 10 have good rate performance, excellent cycle performance and a high 130°C thermal abuse pass rate, which shows that the sulfide monomers of the present invention can introduce disulfide bonds in the generated solid polymers, and the disulfide bonds have dynamic reversibility, and can reform the solid polymer interface protection layer at the cracks of the solid electrolyte interface membrane, thereby effectively self-repairing the solid electrolyte interface membrane, reducing the contact between the positive and negative electrode materials and the organic solvents, lithium salts and other components in the battery, reducing the generation of side reactions and gas inside the battery, increasing the thermal runaway temperature of the battery, and improving the cycle performance and electrochemical performance of the battery.
[0142] From the comparison of Examples 1 to 7 and Comparative Examples 1 and 2, it can be seen that the electrolytes of Examples 1 to 7 contain both acrylate monomers and thioether monomers. The reaction activity between acrylate monomers and thioether monomers is relatively high, which can reduce the residual amount of polymer monomers, reduce the side reactions between the residual polymer monomers and the electrode active materials, and reduce the crosstalk reactions of the residual polymer monomers under the electric field; at the same time, the solid electrolyte interface film is effectively self-repaired, thereby improving the cycle performance and electrochemical performance of the battery.
[0143] From the comparison of Examples 1 to 10 and Comparative Example 3, it can be seen that the sulfide monomers in the electrolytes of Examples 1 to 10 contain carbon-carbon double bonds. The sulfide monomers containing carbon-carbon double bonds have higher reactivity, can increase the conversion rate of the reaction between the sulfide monomers and the acrylate monomers, lower the reaction temperature, reduce the residual polymer monomers in the battery and the side effects of the residual monomers on the battery, and can improve the cycle performance and rate performance of the battery.
[0144] From the comparison between Examples 1 to 3 and Examples 4 and 5, it can be seen that by adding thiol monomers into the electrolyte, the thiol monomers can further consume the thioether monomers, effectively reducing the residual polymer monomers; at the same time, the thiol monomers can undergo an exchange reaction with the disulfide bonds on the solid polymer, causing part of the solid polymer to fold, and the folded solid polymer can coat the surface of the positive and negative electrode material particles with a nano-thin film layer, which is beneficial to reduce the occurrence of side reactions and gas generation inside the battery, reduce the loss of battery capacity, and further improve the electrochemical performance and safety performance of the battery.
[0145] From the comparison between Examples 1 to 3 and Example 10, it can be seen that controlling the contents of acrylate monomers and thioether monomers within an appropriate range can further ensure the electrochemical performance and safety performance of the battery.
[0146] The embodiments of the present invention are described in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.
Claims
1. An electrolyte, characterized in that: include: Organic solvents, lithium salts and polymer monomers; Wherein, the polymer monomers include acrylic ester monomers and thioether monomers, and the structural formula of the thioether monomers is shown in Formula I: wherein n is selected from 2, 3, 4, 5, 6, 7 or 8; y and z are each independently selected from 0, 1, 2, 3, 4, 5 or 6; The substituents R1-R6 are each independently selected from a hydrogen atom, a halogen, a cyano group, an isocyanate group, a C1-C18 substituted or unsubstituted straight or branched alkyl group, a C1-C10 substituted or unsubstituted straight or branched alkoxy group, a C3-C10 straight or branched carboxylate group, a C3-C10 straight or branched acrylate group, a C3-C10 straight or branched alkenyl group, a C3-C10 straight or branched alkynyl group, a C6-C26 unsubstituted aryl group, a C6-C26 aryl group substituted by an alkyl group, an alkoxy group, a hydroxyl group, a cyano group and / or a halogen, a C6-C26 heterocyclic aryl group substituted by an alkyl group, an alkoxy group, a hydroxyl group, a cyano group and / or a halogen, a C7-C27 unsubstituted benzyl group, a C7-C27 benzyl group substituted by an alkyl group, an alkoxy group, a hydroxyl group, a cyano group and / or a halogen, or a combination of these groups.
2. The electrolyte according to claim 1, characterized in that The n is selected from 2 or 3; and / or The y and z are each independently selected from 0 or 1; and / or The substituents R1-R6 are each independently selected from a hydrogen atom and / or a C1-C18 straight or branched alkyl group.
3. The electrolyte according to claim 1, characterized in that The sulfide monomer includes at least one of diethylene disulfide, diallyl disulfide and diallyl trisulfide; and / or The acrylate monomer includes at least one of pentaerythritol tetraacrylate, ethoxylated trimethylolpropane triacrylate, dipentaerythritol hexaacrylate, ditrimethylolpropane tetraacrylate, methyl methacrylate, butyl methacrylate, polyethylene glycol methyl diacrylate, polyethylene glycol methyl diacrylate, and cyanoacrylate.
4. The electrolyte according to claim 1, characterized in that The mass percentage of the polymer monomer in the electrolyte is 2%-34%; and / or The mass percentage of the acrylic ester monomer in the polymer monomer is 30%-85%, and the mass percentage of the thioether monomer in the polymer monomer is 15%-65%.
5. The electrolyte according to any one of claims 1 to 4, characterized in that: The polymer monomers also include thiol monomers.
6. The electrolyte according to claim 5, characterized in that The thiol monomer includes at least one of 1,3-ethanedithiol, benzenethiol, dodecanethiol, 1,4-butanedithiol, 1,6-hexanedithiol, 1,8-octanedithiol, 1,5-pentanedithiol, and 2,3-butanedithiol; and / or The mass percentage of the thiol monomer in the polymer monomer is 0-65%.
7. The electrolyte according to any one of claims 1 to 4, characterized in that: The electrolyte further comprises an initiator and / or an additive.
8. The electrolyte according to claim 7, characterized in that The organic solvent comprises at least one of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, ethylene carbonate, vinylene carbonate, methyl formate, ethyl formate, ethyl acetate, methyl propionate, ethylene glycol dimethyl ether, polyethylene glycol dimethyl ether, ethylene glycol tert-butyl ether, diethylene glycol monomethyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, hexaethylene glycol dimethyl ether, and heptapolyethylene glycol; and / or The lithium salt comprises at least one of lithium nitrate, lithium hexafluorophosphate, lithium perchlorate, lithium difluorooxalatoborate, lithium trifluoromethanesulfonyl imide, lithium bisfluorosulfonyl imide, lithium diacetate borate, lithium tetrafluoroborate, and lithium difluorophosphate; and / or The initiator includes azobisisobutyronitrile, azobisisovaleronitrile, azobisisoheptanenitrile, diethyl azodicarboxylate, di-2-methoxyethyl azodicarboxylate, di-tert-butyl azodicarboxylate, diisopropyl azodicarboxylate, dibenzyl azodicarboxylate, dimethyl azodiisobutyrate, dimethyl azobenzene-4,4'-dicarboxylate, dibenzyl azodihydroxy acid ester, azobisacyldipiperidine, azodicarbonyldimorphine, azodicarbonamide, azobenzene, 4,4-azopyridine, At least one of diethyl 4,4'-azodibenzoate, 4-methyl 4-dimethylaminoazobenzene, 3,3-dimethylazobenzene, phenylazomalononitrile, tert-azobutane, methyl red, methyl orange, tropaeolum orange O, tert-butyl ketone peroxide, cyclohexanone peroxide, dimethanesulfonyl peroxide, tert-butyl perbenzoate, tert-butyl peroxyisopropyl carbonate, 2-butyl ketone peroxide, dilauroyl peroxide, benzoyl peroxide, lithium persulfate, and lithium peroxymonosulfate; and / or The additive comprises at least one of vinylene carbonate, fluoroethylene carbonate, triethyl phosphite, 1,3-propane sultone, ethylene sulfite, 1,3,2-dioxazolethiophene-2,2-dioxide, 1,4-butane sultone, phenyl methanesulfonate, adiponitrile, 3-methoxypropionitrile, hexane-1,3,6-tricarboxonitrile, ethylene glycol bis(propionitrile) ether, hexamethyldisilazane, and trimethylsilyldiethylamine; and / or The mass percentage of the organic solvent in the electrolyte is 30%-80%; and / or The mass percentage of the lithium salt in the electrolyte is 5%-20%; and / or The mass percentage of the initiator in the electrolyte is 0.01%-3%; and / or The mass percentage of the additive in the electrolyte is 2%-30%.
9. An electrolyte, characterized in that The electrolyte is prepared from the electrolyte according to any one of claims 1 to 8.
10. A method for preparing an electrolyte, characterized in that: The following steps are involved: Providing an electrolyte according to any one of claims 1 to 8; The electrolyte is injected into the battery cell, left to stand, and heated to solidify to obtain the electrolyte.
11. The preparation method according to claim 10, characterized in that: The preparation method of the electrolyte comprises the following steps: mixing a formulated amount of an organic solvent, a lithium salt, a polymer monomer and other raw materials to obtain the electrolyte.
12. The preparation method according to claim 11, characterized in that: The other raw materials also include a formulated amount of initiator and / or additives; and / or The mixing is carried out in an argon atmosphere, a nitrogen atmosphere or a dry air atmosphere, and / or the mixing temperature is 20° C.-30° C., and / or the mixing time is 0.5 h-3 h; and / or The standing temperature is 20°C-35°C, and / or the standing time is 24h-72h; and / or The temperature of the heating and curing is 45° C.-120° C., and / or the time of the heating and curing is 8 h-60 h.
13. A lithium ion battery, characterized in that: The electrolyte comprises the electrolyte according to claim 9 or the electrolyte prepared by the method according to any one of claims 10 to 12.
Citation Information
Patent Citations
Aqueous polymer dispersion
CN109563192A
Preparation method of solid-state silicon-lithium battery with long service life
CN113471529A
Self-repairing composite solid-state lithium ion battery electrolyte and preparation method thereof
CN114464880A
Coating apparatus
KR1020250140896A
Cited By
Manganese-based lithium battery, preparation method thereof and power utilization device comprising manganese-based lithium battery
CN120545363A